Slipped capital femoral epiphysis in an adult with congenital hypopituitarism: A case report. Issue 3 (January 2019) - Huang, Yi-Fan; Wang, Li-Shen; Zhang, Shi; Gao, Yu-Hang; Liu, Jian-Guo; Qi, Xin
Abstract: Rationale: Slipped capital femoral epiphysis (SCFE) is a common hip problem in adolescents, usually individuals between 8 and 15 years old. Because of the frequent finding of growth abnormalities in affected children, various endocrine disturbances have been reported as the cause of the disease. However, there are few case reports of older patients in previous literature. To the best of our knowledge, congenital hypopituitarism with normal growth hormone (GH) level has not been reported. Patient concerns: We describe a 29-year-old man who had a 3-month history of pain in the left hip with tall stature and unobvious secondary sexual characteristics. Laboratory testing showed low thyroxine, low cortisol, low follicle-stimulating hormone, low luteinizing hormone, low testosterone, but normal GH. Diagnoses: Brain magnetic resonance imaging showed pituitary hypoplasia. An anteroposterior pelvis radiograph showed severe varus SCFE in the left hip, it was also confirmed with computed tomography scans. Interventions: The patient was treated with levothyroxine, hydrocortisone, and testosterone replacement therapy before surgery. We performed open reduction and anatomical reduction by Dunn's procedure. Outcome: We have followed this patient for 6 months, the left hip mobility gradually improved. No slip in the contralateral proximal femoral physis has been observed. Lessons: When unobvious secondary sexual characteristics and body abnormalities were found in clinical practice, endocrine condition should be evaluated, since the contralateral side may prone to slip due to the lack of endocrine therapy.